INFLUENCE OF SUSTAINABLE DEVELOPMENT VALUES ON YOUNG CHILDREN - Roohi, Tayyibah (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of this study was to investegate the influence of sustainable development values on young children. The study was mixed method and phenomenological method was used. Through judgemental sampling technique, 200 preschool children and eight teachers were selected. An observation checklist was prepared to identify the activities of preschool children about SD and interview protocol was developed to identify, in what way teachers perceived the concept of SD and what was their level of preparedness to combine the values of sustainable development with class room activities. Interviews from eight teachers were documented and transcribed. Both the observation checklist and interview protocol were utilized to attain the data linked to activities of preschool youngsters on the three sturdy pillars (economic, social, and environmental) of education for SD and evaluated with inductive analysis grounded on 17 goals of sustainable development. Participants' children and teachers reflected their ideas about sustainable development. It is recommended that SD rehearses should be incorporated in youngsters curriculum and reinforced by parents and teachers.